The Effect of Online Tracking Systems, Logistics Service Quality, and Complaint Handling on Customer Satisfaction in Goods Delivery Services - Fikri Rafi Rizkia; Muhammad Tohir (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The influence of website-based tracking system, quality of logistics services and complaint handling on customer satisfaction in cargo delivery services is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between independent variables on the dependent variable that will be used in further research. The research object is in online libraries, Google Scholar, Mendeley and other academic online media. The research method with library research is sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) the influence of website-based tracking system affects customer satisfaction; 2) the quality of logistics services affects customer satisfaction; and 3) complaint handling affects customer satisfaction.